BOLAJAQ QARAQALPAQ TILI HÁM ÁDEBIYATÍ OQÍTÍWSHÍSÍNÍŃ PROFILI HÁM OǴAN QOYÍLATUǴÍN MÁMLEKETLIK TALAPLAR - Seytkasımov, D.B. (SCIENCE and SOCIETY, 2023)
The article discusses the mechanism of development of linguistic competence of philology students. Proposals for the development of the language competence of students of the Karakalpak language and literature are given.